Development of Bifunctional Three-Dimensional Cysts from Chemically Induced Liver Progenitors - Yu Huang; Yusuke Sakai; Takanobu Hara; Takeshi Katsuda; Takahiro Ochiya; Tomohiko Adachi; Masaaki Hidaka; Wei-Li Gu; Susumu Eguchi (Stem Cells International)
Chemically induced liver progenitors (CLiPs) have promising applications in liver regenerative medicine. Three-dimensional (3D) structures generated from liver progenitor cells possess wide applications in cell transplantation, disease model, and drug testing. Here, we report on the spontaneous formation of 3D cystic structures comprising maturing rat CLiPs on gelatin-coated dishes. Our 3D cysts contained Alb+/+CK19+/− and Ck19+/+Alb+/− cells. These cell types gradually diverged into specialized mature cells, as demonstrated by the expression of mature biliary markers (Cftr, Ae2, and Aqp1) and hepatic markers (Alb and Mrp2). The 3D cysts also expressed functional multidrug resistance protein 1 (Mdr1), as indicated by epithelial efflux of rhodamine. Furthermore, we observed bile canaliculi functions between hepatocytes and cholyl-lysyl-fluorescein extrusions, indicating that the functional characteristics of 3D cysts and active bile salt export pump (Bsep) transporters were intact. Thus, our study revealed a natural characteristic of rat CLiPs to spontaneously form 3D cystic structures accompanied with cell maturation in vitro, offering a platform for studies of liver development and drug screening.